Feuchtedefizit und Kunstregenbedarf auf niederrheinischen Ökotopen.: Dargestellt am Beispiel der Aldekerker Platte, des Schaephuyser Stauchmoränenwalls und der angrenzenden Niederterrasse - Späth, Hans-Joachim (ERDKUNDE, 1976)
The analysis of the natural soil moisture budget and its variability - preferably based on ten-day periods rather than months - for 1959, 1962, 1966, and 1968 shows that the three typical Lower Rhine regions indeed have moisture deficit periods in spite of the generally humid setting. These periods differ as to their onset, their duration, and the rate of individual sprinkling requirement within any given year. The regulating factor is the soil texture. The Aldekerk Plain (loam) offers the best growing conditions: in all the years analysed its moisture-deficit period started the latest, had the shortest duration, and its deficit rate was the lowest. On the other hand, the terminal moraine of Schaephuysen (loamy-sand to sand) offers distinctively the least favourable soil-hydrological setting for agronomical activities. The Lower Terrace (loam to clay loam) ranks in between these two. As for dry-matter production it is essential to state that the natural actual evapotranspiration rate on the Aldekerk Plain was the highest during all the years. With additional sprinkling the actual evapotranspiration on the Aldekerk Plain and on the Lower Terrace attains to approximately the same annual amount. On the other hand the stimulation of the actual evapotranspiration by sprinkling, and thereby the yield increase, is by far the greatest, and therefore the most economical, on the terminal moraine Schaephuysen. In years with an average precipitation and temperature situation (such as 1968) nutrient transport can be activated only on these sandy soils to a degree (9%) that might justify any investments for sprinkling systems. In years with little precipitation and high temperatures (such as 1959), however, sprinklers could increase the natural actual evapotranspiration on the Aldekerk Plain by about 39%, on the Lower Terrace by 53%, and on the Schaephuysen terminal moraine even by about 71%. Since in reality average climatic settings are found most seldom, and since wet years cannot make up for the deficit of dry years (any moisture surplus above field capacity at the beginning of the growing season is lost), the introduction of sprinklers to any of these regions could in fact effectively meet future pressure on the local food and/or fodder market.